Environmental DNA in the Kuroshio reveals environment-dependent distribution of economically important small pelagic fish - Yu, Zeshu; Wong, Marty Kwok-Shing; Inoue, Jun; Ahmed, Sk Istiaque; Higuchi, Tomihiko; Hyodo, Susumu; Itoh, Sachihiko; Komatsu, Kosei; Saito, Hiroaki; Ito, Shin-ichi (Frontiers in Marine Science, 2023)
Introduction Small pelagic fishes constitute large proportions of fisheries and are important components linking lower and higher trophic levels in marine ecosystems. Many small pelagic fishes in the Northwest Pacific spawn upstream in the Kuroshio and spend their juvenile stage in the Kuroshio Front area, indicating that the Kuroshio Current system impacts their stock fluctuations. However, the distribution of these fish relative to the Kuroshio has not been determined due to dynamic spatio-temporal fluctuations of the system. Here, the recent development of environmental DNA (eDNA) monitoring enabled us to investigate the distribution patterns of four economically important small pelagic fishes (Japanese sardine Sardinops melanostictus, Japanese anchovy Engraulis japonicus, chub mackerel Scomber japonicus, and blue mackerel Scomber australasicus) in the Kuroshio Current system. Methods The influence of environmental factors, such as sea water temperature, salinity, oxygen concentration, chlorophyll-a concentration, and prey fish on the occurrence and quantity of target fish eDNA was analyzed using generalized additive models. In addition, the detection (presence) of target fish eDNA were compared between the offshore and inshore side areas of the Kuroshio axis. Results Sea water temperature showed important effect, especially on the distribution of Japanese sardine and Japanese anchovy, whereas the distribution pattern of chub mackerel and blue mackerel was greatly influenced by the eDNA quantity of Japanese sardine and Japanese anchovy (especially potential prey fish: Japanese anchovy). In addition, we found that the four target fish species could be observed in areas on the inshore side or around the Kuroshio axis, while they were hardly found on the offshore side. Conclusion Based on eDNA data, we succeeded in revealing detailed spatial distribution patterns of small pelagic fishes in the Kuroshio Current system and hypothesized predator–prey relationships influence their distribution in small pelagic fish communities.